EFEK KATERING DIVIDEN - Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Dividend still considered as the main factor affecting the stock price in capital market, because by dividend, the investors will attract for buying or selling their stocks. And by these behaviors, the stock price will fluctuate in capital market. In the other side, managers also believe that, the stock price will increase if they are announcing dividend payment. This phenomenon make the managers tend to behave paying dividends in terms if their stock price valued higher by investors in capital market. In other words, the managers will cater the investors, if in first condition, the investors valuing higher their stock price. This study is using 103 entities listed in Indonesia Stock Exchange in period of 2009 until 2013, and conducting Analysis of Covariate Model (ANCOVA) for hypothesis testing. The results of analysis is show that stock price have significant effect to dividend, while entities with code DP5 are the most entities who significant effect to dividend.